SINTESIS DAN KARAKTERISASI KOMPOSIT TiO2/ZEOLIT SEBAGAI FOTOKATALIS PADA DEGRADASI AMONIA DI DALAM AIR LIMBAH - Adhi Setiawan; Chelvin Sugiarto; Novi Eka Mayangsari; Muhamad Ari; Indri Santiasih (Jurnal Teknologi, 2023)
Ammonia is a wastewater pollutant that can cause oxygen depletion and eutrophication if not treated properly. The Photocatalyst using zeolite-TiO2 was effective method for degrading ammonia compounds in wastewater. This study aimed to analyze the characteristics of the zeolite-TiO2 composite and determine the effect of using the composite in reducing ammonia levels in wastewater. The research were conducted experimentally with a batch process on variations in pH and irradiation time. Data on the decrease in ammonia concentration with time was used to analyze the kinetics of the ammonia degradation reaction. The process of synthesizing zeolite from fly ash using the hydrothermal method. The synthesis of zeolite-TiO2 composites was carried out with a composition ratio of 1:2. Characterization of TiO2/zeolite composites was carried out using SEM-EDX and XRD methods. The results showed that fly ash-TiO2 zeolite composite has a granular morphology, and has an average diameter of 0.257 Î¼m. X-ray diffraction pattern detected peaks in the form of zeolite X and TiO2. The highest ammonia removal efficiency was obtained at pH 11 with an irradiation time of 120 minutes, which was 91.60%. The process of removing ammonia by UV irradiation followed a second-order kinetic model with a k value of 0.1215 (mol.min)-1. The removal of ammonia in dark conditions followed a zero-order kinetic model with a k value of 0.0031 mol.min-1..